A Matter of Time: Father Involvement and Child Cognitive Outcomes. Issue 1 (25th September 2018) - Cano, Tomás; Perales, Francisco; Baxter, Janeen
Abstract : Objective: This study provides the first systematic account of how father–child time (in total and across activity types) relates to children's cognitive development as well as examining whether paternal education moderates these associations. Background: Fathers in Western countries allocate progressively more time to child care. However, most research on how parental time inputs affect child development focuses on maternal time. It remains unclear how paternal involvement in the child's upbringing influences child outcomes. Method: The study uses three waves of unique, longitudinal, time‐diary data from an Australian national sample of children aged 4 to 8 years (Growing Up in Australia: The Longitudinal Study of Australian Children; N = 3, 273 children, 6, 960 observations). Children's cognitive development is measured using the Peabody Picture Vocabulary Test. The data are modeled using a range of estimation strategies for panel data. Results: The total amount of father–child time is associated with, at best, small improvements in children's cognitive functioning. In contrast, the amount of father–child time in educational activities is associated with moderate to large improvements. Such associations are similar for highly and less‐highly educated fathers. Conclusion: Our findings are relevant for policy and practice, being indicative that enabling paternal involvement in their children's upbringing should bring moderate to high gains to their children in terms of cognitive functioning, particularly if paternal involvement is directed at educational activities.